An Exploring IOT Solution for Enhanced Smart Traffic Management System - Akash Maji; Pragati Mahale (MultiTech Publisher, 2023)
This paper delves into the use of the Internet of Things (IoT) to enhance smart traffic management systems. It acts as a middle layer built upon IoT technology, expanding the concept of a smart city by improving traffic light control, parking management, emergency assistance, anti-theft security, and more. IoT facilitates seamless communication between web-connected devices and various components like traffic sensors, services, and actuators, creating a robust network. Consequently, IoT's application in smart traffic management extends beyond just reducing traffic congestion and optimizing traffic flow; it also encompasses continuous monitoring and ensuring the safety of elderly individuals. By collecting data from multiple traffic sources and utilizing IoT, we can analyze traffic patterns, regulate traffic operations, and store valuable insights for future reference. While there are certain limitations to implementing this technology, such as challenges related to advanced machine learning and data-driven techniques, this survey provides a valuable overview of how IoT can be applied to enhance smart traffic management systems, drawing from existing research in the field.